Pengaruh Electronic Word of Mouth Di Tiktok Terhadap Minat Beli Konsumen Di Shopee Pada Era Pandemi Covid-19 Di Kota Bandung - Agustin, Sulistyani; Rusmayanti, Dewi Sri (Asosiasi Ahli Administrasi Indonesia, 2021)
During the COVID-19 pandemic, the number of Shopee and Tiktok users increased. Users use the Tiktok application as a source of information about the products they will buy on Shopee e-commerce. Therefore, this study aims to examine the effect of electronic word of mouth (eWOM) on online consumer buying interest. This research uses a quantitative descriptive method using a questionnaire measuring instrument. A total of 116 TikTok and Shopee users in the Greater Bandung area were involved in this study. Furthermore, data analysis using the SPSS v.26 application checks the validity and reliability tests, normality, and simple regression analysis. The results of data analysis showed that electronic word of mouth (eWOM) has a positive and significant influence on online consumer buying interest.